Intramolecular C–H arylation of pyridine derivatives with a palladium catalyst for the synthesis of multiply fused heteroaromatic compounds - Yuki Nakanishi; Shoichi Sugita; Kentaro Okano; Atsunori Mori (Beilstein Journal of Organic Chemistry)
The C–H arylation of 2-quinolinecarboxyamide bearing a C–Br bond at the N-aryl moiety is carried out with a palladium catalyst. The reaction proceeds at the C–H bond on the pyridine ring adjacent to the amide group in the presence of 10 mol % Pd(OAc)2 at 110 °C to afford the cyclized product in 42% yield. The yield is improved to 94% when the reaction is performed with PPh3 as a ligand of palladium. The reaction is examined with amides derived from unsubstituted picoline, 6-methylpicoline, and 2,6-pyridinedicarboxylic acid in a similar manner to afford the cyclized products in 70%, 77%, and 87% yield, respectively. The related reaction is also carried out with amides of non-pyridine derivatives terephthal- and benzamides to afford multiply fused heterocyclic compounds in 81% and 89% yields, respectively.